PELAKSANAAN FUNGSI PENGADILAN NIAGA DALAM PENYELESAIAN PERKARA KEPAILITAN (Suatu Analisis di Pengadilan Niaga Medan) - M. Jazuri, Dahlan, Yusri Z. Abidin. (Jurnal Ilmu Hukum, 2013)
Abstract: In May 1997 the monetary crisis that hit many parts state of the world including Indonesia. Due to the monetary crisis in Indonesia are many companies that went bankrupt. As a company typically known for their activities in need of loan funds from some other company that is known by the term debtor and creditors. As a result of this crisis is often Debtors unable to pay off his debts. To prevent looting and seize each other among some creditors will require the existence of a legal rule that can be used in a speedy, fair, open and efficient. So that the government establish a legal rule that is The Government Regulation as Replacement Act Number 1, 1998, then passed by the Act Number 4, 1998 and and revised to be the Act Number 37, 2004 on Bankruptcy and Suspension of Payment (PKPU). Under Article 7 the Act Number 37, 2004 is authorized to hear and rule on cases of bankruptcy and Suspension of Payment is Trading Court that is within GeneralCourt. Based the provisions of Article 281 paragraph (1) The Government Regulation as Replacement Act Number 1, 1998 Jo Act Number 4, 1998 was first established at the Central Jakarta District Court. Furthermore, based on the Presidential Decree Number 97, 1999, established of 5 (five) other Trading Court, they are the Trading Court of Ujung Pandang (Makassar), the Trading Court of Medan, the Trading Court of Surabaya and the Trading Court of Semarang. In fact, with the revisions to the Bankruptcy Rules of the Trading Court of Medan capable of resolving Trading disputes in a fair, fast, open and effective? This paper aims at reviewing the existing reality in the implementation of the Bankruptcy Act in the Trading Court of Medan whether to provide legal certainty as expected by the Bankruptcy Act to the business world for both the debtor and creditors and also for the people of Indonesia in general. Are there any constraints are found and how to handle it. To obtain the data in this study conducted with 2 (two) ways, namely: Library Research and Field Research. The literature research carried out in order to obtain secondary data, through a review of legislation, literature, literature, research works, journal of legal experts who have anything to do with this research. While field studies to obtain primary data, obtained by conducting interviews with informants and respondents. The results showed that the Trading Court of Medan has been carrying out the applicable provisions of the act number 37, 2004 on Bankruptcy and Suspension of Payment. but there are some provisions that are difficult to be implemented such as the calling period of the parties and the examination process. In addition there were a few rules in the Bankruptcy Act and the Suspension of Payment are also a couple of conflicting rules in the Act which conflict with other act. Human Resources is also a barrier. Limitations of judges and court staff in the almost the trial schedule another case resulted in judges and court staff should be smart divide the trial schedule. To an external court advocates and curator are still very few professional who has a certificate in the completion of the bankruptcy case and understand the rules of bankruptcy. Substantial costs are also an obstacle for creditors to use bankruptcy institution. The Government Regulation to issue the implementing rules supporting this bankruptcy case is still low, such as the implementing regulation of the effort to force the body (Gijzeling) which until now has not been published. The results showed that the Trading Court of Medan has been carrying out the applicable provisions of the Act Number 37, 2004 on Bankruptcy and Suspension of Payment, but there are some rules that take very different, especially regarding the limits of the parties and calls on the definition of "debt" that own. Are the bottlenecks in the implementation of this law is the lack of staff in the Trading Court of Medan as well as perceptions of inequality among the judges of the Trading Court of Medan will the definition of "debt" and understanding of the creditors. In addition there are very few lawyers who mastered the Law of Procedure in case of bankruptcy proceedings and Suspension of Payment as well as the refusal of the debtor and the creditor on the bankruptcy property settlement made by the Curator. It is suggested to the government to improve again the provisions of the Act Number 37, 2004 and implementing regulations, especially regulations implementing agency of the effort force (Gijzeling), additional facilities and infrastructure to support the bankruptcy dispute resolution, implementation of education and training of judges and lawyers bankruptcy, the implementation of seminars and discussions to resolve the obstacles that were found and debriefing training for the Receiver. Keywords : The Trading Court, Bankruptcy, Debt, Creditor, Debitor Abstrak: Pada bulan Mei 1997 terjadi krisis moneter yang melanda sebagian besar negara di dunia termasuk Indonesia. Akibat terjadinya krisis moneter tersebut banyak perusahaan di Indonesia yang mengalami kebangkrutan. Sebagaimana diketahui lazimnya suatu perusahaan dalam melaksanakan kegiatannya membutuhkan dana pinjaman dari beberapa perusahaan lain sehingga dikenal dengan adanya istilah Debitor (si peminjam utang) dan kreditor (si pemberi utang). Akibat terjadinya krisis ini tidak jarang Debitor tidak mampu melunasi utang-utangnya. Untuk mencegah terjadinya perampasan dan saling rebut diantara beberapa kreditor maka diperlukan adanya suatu aturan hukum yang dapat digunakan secara cepat, adil, terbuka dan effisien. Untuk itu pemerintah membentuk suatu aturan hukum yaitu PERPU Nomor 1 Tahun 1998 yang kemudian disahkan dengan Undang-Undang Nomor 4 Tahun 1998 dan direvisi lagi menjadi Undang-Undang Nomor 37 Tahun 2004 tentang Kepailitan dan Penundaan Kewajiban Pembayaran Utang. Berdasarkan Pasal 7 Undang-Undang Nomor 37 Tahun 2004 maka yang berwenang untuk mengadili dan memutus perkara kepailitan dan Penundaan Kewajiban Pembayaran Utang adalah Pengadilan Niaga yang berada di bawah lingkungan Peradilan umum. Berdasarkan ketentuan Pasal 281 ayat (1) PERPU Nomor 1 Tahun 1998 Jo Undang-undang Nomor 4 Tahun 1998 pertama kali dibentuk Pengadilan Niaga Jakarta Pusat. Selanjutnya berdasarkan Keputusan Presiden (Keppres) RI No.97 Tahun 1999 di bentuk 5 (lima) Pengadilan Niaga lainnya yaitu Pengadilan Niaga Ujung Pandang (Makassar), Pengadilan Niaga Medan, Pengadilan Niaga Surabaya dan Pengadilan Niaga Semarang. Dalam kenyataannya dengan adanya revisi terhadap Peraturan Kepailitan tersebut apakah Pengadilan Niaga Medan mampu menyelesaikan sengketa niaga secara adil, cepat, terbuka dan efektif ? Penulisan ini bertujuan meninjau kenyataan yang ada dalam pelaksanaan Undang-Undang Kepailitan di Pengadilan Niaga Medan apakah telah memberikan kepastian hukum sesuai dengan yang diharapkan oleh Undang-Undang Kepailitan bagi dunia usaha baik bagi debitur maupun kreditur dan juga bagi masyarakat Indonesia pada umumnya. Apakah ada hambatan-hambatan yang ditemukan serta bagaimana cara mengatasinya. Untuk memperoleh data dalam penelitian ini dilakukan dengan 2 (dua) cara, yaitu : Penelitian Kepustakaan (Library Research) dan Penelitian Lapangan (Field Research). Penelitian Kepustakaan dilaksanakan guna mendapatkan data-data sekunder, melalui pengkajian terhadap peraturan perundang-undangan, literature-literatur, karya-karya penelitian, tulisan-tulisan para pakar hukum yang ada kaitannya dengan penelitian ini. Sedangkan penelitian lapangan untuk memperoleh data primer, diperoleh dengan cara melakukan wawancara dengan informan dan responden. Hasil penelitian menunjukan bahwa Pengadilan Niaga Medan telah melaksanakan ketentuan yang berlaku dalam Undang-undang No 37 Tahun 2004 tentang Kepailitan dan Penundaan Kewajiban Pembayaran Utang. namun ada beberapa ketentuan yang susah untuk dilaksanakan seperti misalnya jangka waktu pemanggilan para pihak maupun proses pemeriksaannya. Selain itu ternyata ada beberapa aturan dalam Undang-undang Kepailitan dan Penundaan Kewajiban Pembayaran Utang itu yang saling bertentangan juga ada beberapa aturan dalam Undang-undang tersebut yang bertentangan dengan aturan hukum lain. Sumber Daya Manusia juga menjadi hambatan. Keterbatasan hakim serta staff pengadilan di tengah menumpuknya jadwal persidangan dan perkara lainnya mengakibatkan hakim dan staff pengadilan harus pintar membagi jadwal persidangan. Untuk eksternal Pengadilan masih sangat sedikit advokat dan kurator yang profesional memiliki sertifikat dalam penyelesaian perkara kepailitan dan memahami aturan kepailitan. Biaya yang besar juga menjadi hambatan bagi para kreditor untuk mempergunakan lembaga kepailitan ini. Peran pemerintah untuk menerbitkan aturan pelaksana pendukung perkara kepailitan ini juga masih rendah seperti misalnya aturan pelaksana tentang upaya paksa badan (Gijzeling) yang sampai sekarang belum diterbitkan. Di sarankan kepada pemerintah untuk menyempurnakan lagi ketentuan dalam Undang-undang No 37 Tahun 2004 serta peraturan pelaksananya terutama peraturan pelaksana tentang upaya paksa badan (Gijzeling), penambahan sarana dan prasarana pendukung dalam penyelesaian persengketaan kepailitan, pelaksanaan pendidikan dan pelatihan hakim Niaga dan para advokat kepailitan, pelaksanaan seminar-seminar dan diskusi guna menyelesaikan hambatan yang di temukan dan pembekalan pelatihan bagi para Kurator. Kata kunci : Pengadilan Niaga, Kepailitan, Kreditor, Debitor, Utang